2019
DOI: 10.1073/pnas.1818401116
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vpr counteracts HLTF-mediated restriction of HIV-1 infection in T cells

Abstract: Lentiviruses, including HIV-1, possess the ability to enter the nucleus through nuclear pore complexes and can infect interphase cells, including those actively replicating chromosomal DNA. Viral accessory proteins hijack host cell E3 enzymes to antagonize intrinsic defenses, and thereby provide a more permissive environment for virus replication. The HIV-1 Vpr accessory protein reprograms CRL4DCAF1 E3 to antagonize select postreplication DNA repair enzymes and activates the DNA damage checkpoint in the G2 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 83 publications
1
39
0
Order By: Relevance
“…Previous studies suggested that HIV-1 Vpr antagonizes several post-replication DNA repair machineries by usurping the CRL4-DCAF1. Importantly, recent reports showed that removal of HLTF and EXO1 is beneficial to HIV-1 replication (26,33). The observation that removal of these proteins only partially accounts for the phenotypic effect of Vpr implicates the existence of additional Vpr-counteracted machineries that restrict viral replication.…”
Section: Several Studies Have Suggested a Functional Link Between Hismentioning
confidence: 99%
“…Previous studies suggested that HIV-1 Vpr antagonizes several post-replication DNA repair machineries by usurping the CRL4-DCAF1. Importantly, recent reports showed that removal of HLTF and EXO1 is beneficial to HIV-1 replication (26,33). The observation that removal of these proteins only partially accounts for the phenotypic effect of Vpr implicates the existence of additional Vpr-counteracted machineries that restrict viral replication.…”
Section: Several Studies Have Suggested a Functional Link Between Hismentioning
confidence: 99%
“…Recently, it was found that HIV-1 Vpu targets additional ISGs including CD99, PLP2, and UBE2L6 for proteolytic degradation in a manner mechanistically similar to antagonism of BST2 [99][100][101][102]. HIV-1 Vpr and its Vpr/Vpx homologs in HIV-2 and SIV associate with the cullin4A-DDB1-DCAF1 complex to target multiple host factors including tet methylcytosine dioxygenase 2 (TET2) and helicase-like transcription factor (HLTF) for degradation, thus promoting virus infection [103,104]. This interaction is also essential for Vpx-induced degradation of SAMHD1, facilitating reverse transcription in myeloid and resting T cells, as mentioned above [18,19,105].…”
Section: Counteraction Of Hiv-1 Restriction Factorsmentioning
confidence: 99%
“…Vpr causes ubiquitination and subsequent proteasomal degradation of helicase-like transcription factor (HLTF), a multi-domain, multi-functional protein that activates post-replication DNA repair [156,157]. Vpr-mediated degradation of HLTF enhances HIV replication in CD4 + T cells, but this effect is only apparent in competition assays [158]. Moreover, silencing HLTF did not fully restore replication by the Vpr mutant, indicating that Vpr has additional functions.…”
Section: Vpr's Role In Viral Replicationmentioning
confidence: 99%